Ideas and power: shaping monetary policy in South Africa 1919-1936 - Bordiss, Bradley John (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2026)
In the concluding paragraphs of Keynes' General Theory, Keynes suggests that vested interests (power) may dominate in the short term, but that "sooner or later, it is ideas, not vested interests, which are dangerous for good or evil" (Keynes
Keywords: Monetary policy -- South Africa -- 1919-1936; Economic development -- South Africa -- 1919-1936; Economics -- South Africa -- History; Economics -- Philosophy; South Africa -- Economic policy -- 1919-1936; South Africa -- Foreign economic relations -- 1919-1936; Great Britain -- Foreign economic relations --1919-1936; Great Britain -- Economic policy -- 1918-1945